2023
DOI: 10.3390/cancers15174302
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alpha-Fetoprotein (AFP) in Diagnosing Childhood Cancers and Genetic-Related Chronic Diseases

Joanna Głowska-Ciemny,
Marcin Szymanski,
Agata Kuszerska
et al.

Abstract: Alpha-fetoprotein (AFP) is a protein commonly found during fetal development, but its role extends beyond birth. Throughout the first year of life, AFP levels can remain high, which can potentially mask various conditions from the neurological, metabolic, hematological, endocrine, and early childhood cancer groups. Although AFP reference values and clinical utility have been established in adults, evaluating AFP levels in children during the diagnostic process, treatment, and post-treatment surveillance is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…The level AFP of this patient was 1,439 ng/ml. In pediatric patients, HCC levels of AFP are high in 50-92% of cases (Czauderna et al, 2002;Głowska-Ciemny et al, 2023). In this case, the diagnosis of HCC was established based on history of chronic hepatitis B with HbsAg positive.…”
Section: Discussionmentioning
confidence: 95%
“…The level AFP of this patient was 1,439 ng/ml. In pediatric patients, HCC levels of AFP are high in 50-92% of cases (Czauderna et al, 2002;Głowska-Ciemny et al, 2023). In this case, the diagnosis of HCC was established based on history of chronic hepatitis B with HbsAg positive.…”
Section: Discussionmentioning
confidence: 95%
“…This has been debated for children with Beckwith-Wiedemann syndrome (BWS) 2,6 ; however, most concerns raised about routine AFP surveillance are applicable to SGBS as well. 9 European guidelines for hepatoblastoma screening in BWS highlight challenges with AFP test interpretation, lack of precise reference ranges (AFP levels are increased in a number of genetic disorders, [10][11][12][13][14][15] with established reference range only for BWS), 10 the invasiveness of frequent blood draws, and unproven utility compared with imaging. 7,8 In contrast, North American guidelines argue that AFP elevation may precede detection of a mass on imaging, leading to a more timely diagnosis, 16 lower stage, and improved prognosis.…”
Section: E T T E R T O T H E E D I T O R a Case Of Pancreatoblastoma ...mentioning
confidence: 99%
“…In many studies, confirmation of AFP as a useful marker of various pathologies could be found. In clinical practice, AFP is used as a tumor and gestational marker; however, more and more research studies have indicated a relationship between AFP levels and ovarian masses ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%